Technology of Implementation of the Pitched Green Roof on the Testing Building EnviHut - Selník, Petr; Selníková, Klára; Mohapl, Martin (Elsevier, 2016)
The idea of green roofs with simple application aims for expansion of using green roofs in the contemporary construction industry. The local climatic conditions of larger urban units may be positively affected due to numerous incidences of these structures. The application of environmentally friendly materials of green roofs dramatically increases economic costs of a whole project in this time. This article describes one of the possible solutions that would minimize the effect of the negative aspects mentioned above. The technology of testing installation was carried out in a residential research project EnviHUT. The inclination of the gable roof is 30°. The project EnviHUT is designed as a self-sufficient mobile unit that can be used for example as a weekend recreation facility. A more detailed description of the testing installation is a part of this article. The process of continues monitoring is regularly restored by the team of Brno University of Technology and more information is indicated on the website. Three variants of green roofs - extensive sedum roof, biodiverse semi-intensive roof and roof made up from turf carpets were implemented on the described building EnviHUT. Each layer's set of the examined vegetation layer system shows different building-physical characteristics and also different properties from architectural and also botanical perspectives. The tested vegetative-retention mats are made from recycled polyester fibres and they are a part of all the above mentioned variants of green roofs. This solution allows to simplify and speed up the installation of the pitched and flat green roofs and it also provides a high level of protection of waterproofing layers during installation.

The idea of green roofs with simple application aims for expansion of using green roofs in the contemporary construction industry. The local climatic conditions of larger urban units may be positively affected due to numerous incidences of these structures. The application of environmentally friendly materials of green roofs dramatically increases economic costs of a whole project in this time. This article describes one of the possible solutions that would minimize the effect of the negative aspects mentioned above. The technology of testing installation was carried out in a residential research project EnviHUT. The inclination of the gable roof is 30°. The project EnviHUT is designed as a self-sufficient mobile unit that can be used for example as a weekend recreation facility. A more detailed description of the testing installation is a part of this article. The process of continues monitoring is regularly restored by the team of Brno University of Technology and more information is indicated on the website. Three variants of green roofs - extensive sedum roof, biodiverse semi-intensive roof and roof made up from turf carpets were implemented on the described building EnviHUT. Each layer's set of the examined vegetation layer system shows different building-physical characteristics and also different properties from architectural and also botanical perspectives. The tested vegetative-retention mats are made from recycled polyester fibres and they are a part of all the above mentioned variants of green roofs. This solution allows to simplify and speed up the installation of the pitched and flat green roofs and it also provides a high level of protection of waterproofing layers during installation.
Technology of Implementation of the Pitched Green Roof on the Testing Building EnviHut
Keywords: zelená střecha; technologický postup; vegetačně-retenční deska; záchytný systém; zelená střecha; technologický postup; vegetačně-retenční deska; záchytný systém